2020
DOI: 10.1111/ppe.12627
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping congenital anomalies in administrative hospital records

Abstract: Background: Congenital anomalies are a major cause of co-morbidity in children.Diagnostic code lists are increasingly used to identify congenital anomalies in administrative health records. Evidence is lacking on comparability of these code lists. Objectives:To compare prevalence of congenital anomalies and prognostic outcomes for children with congenital anomalies identified in administrative health records using three different code lists. Methods:We developed national cohorts of singleton livebirths in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…gestational age, sex, maternal age and area-level deprivation, comparable with information recorded in birth registers in the Nordic countries, Scotland, Canada and Australia, although improvements to data completeness are needed. Diagnoses are coded using ICD-10 classification, which is also used in hospital records in Europe, New Zealand, Australia and Canada [18], enabling international comparisons of child health outcomes (such as mortality, congenital anomalies, chronic conditions or respiratory tract infections) [4,5,8,10,53].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…gestational age, sex, maternal age and area-level deprivation, comparable with information recorded in birth registers in the Nordic countries, Scotland, Canada and Australia, although improvements to data completeness are needed. Diagnoses are coded using ICD-10 classification, which is also used in hospital records in Europe, New Zealand, Australia and Canada [18], enabling international comparisons of child health outcomes (such as mortality, congenital anomalies, chronic conditions or respiratory tract infections) [4,5,8,10,53].…”
Section: Plos Onementioning
confidence: 99%
“…Whole-country coverage minimises selection bias and loss to follow-up [1], and enables developing "natural experiments" to assess the impact of policy changes and public health interventions on population health [2,3]. Large sample size enables studying rare outcomes, such as child mortality or congenital anomalies [4,5]. Further, secondary use of routinely collected data reduces study costs and time compared to de novo data collection.…”
Section: Introductionmentioning
confidence: 99%
“…77 The prevalence of CMs was shown to depend markedly on the code-list applied, ranging from 1.8% to 4.1%. 77…”
Section: Discussionmentioning
confidence: 98%
“…The influence of the codes used is also pertinent to studies of secondary care data. A very recent study, published after we completed the search for this review, identified CMs in UK hospitalisation data using three different ICD‐10 code‐lists 77 . The prevalence of CMs was shown to depend markedly on the code‐list applied, ranging from 1.8% to 4.1% 77 …”
Section: Discussionmentioning
confidence: 99%
“…Cases were classified as isolated or complex depending on the presence of additional congenital anomaly diagnoses recorded in hospital or death records during infancy (online supplemental table 4). 20 Codes related to anorectal conditions were excluded from this classification.…”
Section: Methodsmentioning
confidence: 99%